An unusual finding of necrosis in an inflammatory pseudotumour - Seneviratne, B.; Gamage, B.; Rajapakse, A. (My University, 2015)
Attached

Introduction : Inflammatory pseudotumour is a rare, chronic inflammatory disorder and is not considered a true neoplasm. It is frequently encountered in the first two decades o f life and is related to an infective process or a foreign body reaction. Clinical behavior is unpredictable, ranging from benign to a locally aggressive lesion. Case history : A 20 year old female presented with a vague, right side loin pain for 2 months duration. She was diagnosed as having a retroperitoneal mass attached to the right adrenal gland by imaging studies. Pathological findings : Resected specimen was a well-circumscribed, yellow-brown soft tissue mass weighing 19.1g and measuring 37 x 25x 15mm. Microscopic examination showed a spindle cell lesion mixed with plasma cells, lymphocytes, histiocytes and foreign body giant cells. Focal myxoid change, reactive vascular proliferation and a large area o f necrosis was seen. The mitotic count was <1/10 high power fields. Discussion : Histological differential diagnoses included an inflammatory pseudotumour, a lowH'mde-sarcoma, a solitary fibrous tumour or a chronic granulomatous condition. Immunohistochemistry showed negativity for CD 34 and desmin and focal positivity for SMA. I tie Ki 67 index was < 2%.